GeMSE: a low-background facility for gamma-spectrometry at moderate rock overburden. (1st April 2022) - Ramírez García, D.; Baur, D.; Grigat, J.; Hofmann, B.A.; Lindemann, S.; Masson, D.; Schumann, M.; von Sivers, M.; Toschi, F.
Abstract: The GeMSE (Germanium Material and meteorite Screening Experiment) facility operates a low-background HPGe crystal in an underground laboratory with a moderate rock overburden of 620 m.w.e. in Switzerland. It has been optimized for continuous remote operation. A multi-layer passive shielding, a muon veto, and a boil-off nitrogen purge line inside the measurement cavity minimize the instrument's background rate, which decreased by 33% to (164 ± 2) counts/day (100 – 2700 keV) after five years of underground operation. This agrees with the prediction based on the expected decay of short-lived isotopes. A fit to the known background components, modeled via a precise simulation of the detector, shows that the GeMSE background is now muon-dominated. We also present updates towards a more accurate detection efficiency calculation for the screened samples: the thickness of the crystal's outer dead-layer is precisely determined and the efficiency can now be easily calculated for any sample geometry. The advantage of this feature is showcased via the determination of the 40 K content in the screening of a complex-shaped object: a banana.